Cricket, the Retired Feather Merchant, and Settler Colonialism: The Troubled Halifax Sojourn of A.H. Leighton, 1912 - Reid, John (Acadiensis, 2017)
In Canadian sport historiography, cricket is frequently characterized as uniformly elitist. Yet in Nova Scotia the sport was socially complex, as shown in 1912 by the Halifax career of A.H. Leighton. A professional player with an elite club, the Wanderers, Leighton’s condescending behaviour stirred up dissension with players elsewhere who resented his and the club’s social pretensions. Leighton’s brief and troubled sojourn provides a revealing window on a sport that reflected settler colonial aspirations but in which class-related social tensions ran deep. It also illustrates the nature of the unregulated global market for professional cricketers.